2021
DOI: 10.1002/adma.202106732
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Elastomer Tunes Phase Structure and Promotes Stretchability of High‐Efficiency Organic Solar Cells

Abstract: the power conversion efficiencies (PCEs) of OSCs show rapid increase and the values have increased to over 18%. [16][17][18][19][20][21][22][23][24] However, owing to the brittle nature of small molecules, [25] the mechanical properties of polymer:NF-SMA blends are generally insufficient and can hardly meet the requirement of stretchable electronics. [26,27] The mechanical imperceptibility of OSCs requires low stiffness and high extensibility for wearable and portable applications. The human skin exhibits a du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 77 publications
(122 reference statements)
3
133
0
Order By: Relevance
“…Ye and coworkers comprehensively investigated the influence of SEBS (polystyrene-blockpoly(ethylene-ran-butylene)-block-polystyrene) in different BHJ blended systems. [13] They demonstrated that the incorporation of thermoplastic elastomers in the BHJ systems was a universal strategy to improve the stretchability, reduce the elastic modulus, and maintain the photovoltaic performance. Moreover, the changes in mechanical and photovoltaic properties have been ascribed to the morphology evolutions of the composite systems.…”
mentioning
confidence: 99%
“…Ye and coworkers comprehensively investigated the influence of SEBS (polystyrene-blockpoly(ethylene-ran-butylene)-block-polystyrene) in different BHJ blended systems. [13] They demonstrated that the incorporation of thermoplastic elastomers in the BHJ systems was a universal strategy to improve the stretchability, reduce the elastic modulus, and maintain the photovoltaic performance. Moreover, the changes in mechanical and photovoltaic properties have been ascribed to the morphology evolutions of the composite systems.…”
mentioning
confidence: 99%
“…Insertion of insulating breaking spacers (e.g., alkyls) to the backbones of conjugated polymers has been provided as a means to address the low ductility of Y6-based polymer acceptors. Besides, systematically characterizing the mechanical properties [104][105][106][107] of these polymer donors and acceptors might aid in the development of flexible and stretchable all-PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The film morphology of polymer blends not only affects the PCE of All-PSCs but also closely determines their mechanical property and stability. Revealing the fundamental connections between morphological parameters at different length scales and mechanical parameters 170,171 (elastic modulus, fracture energy, crack-onset strain, cohesion energy, toughness, and so on) warrants in-depth explorations. In future studies, a full set of polymer structure-morphology-property correlations should be further clarified to provide design rules for commercially viable novel All-PSCs.…”
Section: • Determining the Interaction Parameters And Molecular Misci...mentioning
confidence: 99%